Failure and Acoustic Emissions of Coal–Rock Combinations with Different Dip Angles in the Shaqu No. 1 Coal Mine - Yuping Fu; Yongliang He; Chuantian Li (Advances in Civil Engineering, 2023)
The force and deformation characteristics of the rock layer on the top and bottom of the coal seam change significantly when the dip angle changes. The mechanical properties and damage characteristics of differently inclined coal–rock assemblages were investigated, and the results were combined with acoustic emission information, including acoustic emission ringdown counts, to quantify the damage of inclined coal–rocks under compression. The experimental results showed that the stress‒strain curves of the inclined coal–rock assemblages had four main stages, with approximately similar curves in the early stage and deformation in the later stage. The damage gradually changed from shear damage to interfacial slip damage, and the damage area gradually transitioned to the structural surface from coal body components. The cumulative acoustic emission energy tended to decrease with increasing inclination angle, and the peak acoustic emission energy gradually decreased. When the inclination angle was less than 30°, the cumulative energy of acoustic emissions increased slowly, then decreased, and it finally decreased significantly between 30° and 45°; from 0° → 15° → 30° → 45°, the energy change rates were +3.0%, −25.1%, and −78.2%, respectively. For coal–rock assemblages with different interfacial angles, the sliding damage instability caused by the coal–rock interface increased with increasing interfacial angle within the assemblage. The results of this study provide a deeper understanding of the mechanical properties of coal–rock assemblages with different inclinations and the characteristics of fissure extension. The fractal dimension based on particle number decreased with increasing loading rate, and the larger the loading rate was, the smaller the fractal dimension. In addition, the current findings provide a reliable foundation for further understanding the mechanisms of disasters caused by coal–rock disturbances, such as excavation of inclined roadways and extraction of gas, as well as supporting the development of methods for monitoring, early warning, and prevention and control of these types of disasters.